2012
DOI: 10.3168/jds.2011-5241
|View full text |Cite
|
Sign up to set email alerts
|

Candidate mechanisms underlying atypical progesterone profiles as deduced from parameter perturbations in a mathematical model of the bovine estrous cycle

Abstract: The complex interplay of physiological factors that underlies fertility in dairy cows was investigated using a mechanistic mathematical model of the dynamics of the bovine estrous cycle. The model simulates the processes of follicle and corpus luteum development and its relations with key hormones that interact to control these processes. Several factors may perturb the regular oscillatory behavior of a normal estrous cycle, and such perturbations are likely the effect of simultaneous changes in multiple param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…The next step is to characterise how and why the components are interlinked. One approach is to explore the underlying mechanisms, for example, associating production with reproduction (Boer et al, 2012). This is extremely useful for linking key robustness mechanisms to gene expression and genomics.…”
Section: Friggens Blanc Berry and Puilletmentioning
confidence: 99%
“…The next step is to characterise how and why the components are interlinked. One approach is to explore the underlying mechanisms, for example, associating production with reproduction (Boer et al, 2012). This is extremely useful for linking key robustness mechanisms to gene expression and genomics.…”
Section: Friggens Blanc Berry and Puilletmentioning
confidence: 99%
“…Bien que les facteurs majeurs (production laitière, bilan énergétique…) influençant la fertilité soient identifiés, les mécanismes physiologiques sous-jacents sont encore mal connus (Friggens et al 2010a). Néanmoins, les modèles systémiques de la physiologie de la reproduction peuvent être utilisés pour identifier les mécanismes potentiellement impliqués dans divers types de profils hormonaux anormaux (Boer et al 2012. Cette stratégie est puissante, non seulement pour rechercher des biomarqueurs, mais aussi pour explorer les différentes voies métaboliques par lesquelles les facteurs environ-nementaux et les compromis entre fonctions peuvent influer sur la reproduction.…”
Section: / Définir De Nouveaux Critères Associés à La Robustesseunclassified
“…A systems modeling approach to reproduction was used in several studies (as reviewed in Vetharaniam et al, 2010). More recently, deterministic mathematical models for cattle reproduction were proposed by Boer et al (2011aBoer et al ( , 2011bBoer et al ( and 2012 and Martin et al (2012), and these groups noted that these models could be used as a framework for studying nutritional and physiological effects on estrus cyclicity. The mathematical model by Boer et al (2011aBoer et al ( , 2011bBoer et al ( and 2012 describes the dynamics of the bovine estrous cycle as a set of linked differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…As a first step in model validation, Boer et al (2011b) demonstrated that it is possible to find parameter values that can simulate a normal 'average' cow. A further test of the model was to demonstrate that it is possible to find parameter values able to simulate disruptions of normal cyclicity like cystic ovaries (Boer et al, 2012). Furthermore, the model was validated by simulating estrous cycle synchronization protocols based on prostaglandin F2α analogue (PGF2α) administration (Stötzel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation